(untitled) (Heritage, 2024)
In 1908, in Turkey, Young Turk revolution was carried out. Young Turk revolution won and it seemed that it will lead to the transformation of society and that liberal thoughts will be adopted. However, the Young Turk regime restricted even more and more the rights of Serbian population in Beran casa which caused great disappintment. In the middle of July in 1909 a new vice vizier Nuri-bey, who issued several orders. came to Berane. He forbidden wearing caps with initials NI (Nikola I), he ordered that every citizen of Turkish Empire is obligated to take nufuz, in fact, it is a list of demands by the Turkish Empire in order to start collecting lagged taxes, he also limited the possibilities of getting in and getting out from Beran nahija to Montenegro in such a way that there was only one border crossing instead of three and that one demanded passports.Carryng weapons was forbidden for Montenegro citizens who enter the territory of Turkey, as it was before. Schools in Beran nahija which were under control of Rasko – Prizren archbishop, but were financed by governments of Serbia and Montenegro, came to blow of Turkish politics. In order to settle accounts with orthodox population in Beran casa, vice vizier used an incident (shooting from fire weapon) that happened at Assumtion parliament at Djurdjevi stupovi monastery on 15(28) August 1909. About 800 of those present citizens at the parliament were announced as asije (renegades). The explanation for this was that Lower Vasojevic population had intention to lead out the annex of Beran casa to Montenegro. In all Serbian villages he put millitary guards that terrorized Serbian population. In June 1910 mutesarif Ismail Haki-bey came to Berane. Since he became familiar with the situation in Beran nahija, a few days later he annonced urfija (court martial). He ordered Serbian houses to be searched and to be arrested all those people who had weapons. He arrested 18 people in total. He also ordered that tomorrow on 16 June whole population came out in the street. Army took out arrested Serbs and hit them. Their families and relatives had to watch because the cordon of army surrounded the people. In order to show how determined he was, mutesarif ordered the search in all the houses and the arrest of all those who had weapons.When people heard what had happened in Berane, they ran away. This terror of Turkish authorities led to new emigrations, so the number of refugees on Montenegrinian territory kept rising. Montenegrinian government authorised border commissar in Andrijevica Radomir Vesovic to take over negotiations with Turkish authorities on emigration returnees. On 17 May Radomir Vesovic and Beran vice vizier first met in Vinickoj, and on 22 May in Berane. It is agreed that emigrants could go back to their properties, except for those 83 who were accused. That was the ending of “Beran affair” which brought great sufferring and destruction.